Cuba after Castro : legacies, challenges, and impediments - Gonzalez, Edward (RAND Corp., 2004)
Cuba is nearing the end of the Castro era. When that end arrives, the government that succeeds Fidel Castro, as well as the Cuban people themselves, will need answers to the following questions: How is Castro's more than four-decade rule likely to affect a post-Castro Cuba? What are the political, social, and economic challenges that Cuba will have to confront? What are the impediments that will need to be surmounted if Cuba is to develop economically and embark on a democratic transition? To answer those questions, the authors examine Castro's political legacies, Cuba's generational and racial divisions, its demographic predicament, the legacy of a centralized economy, and the need for industrial restructuring. They conclude by offering policy guidelines for the United States to foster a stable and prosperous post-Castro Cuba.